Thermal Performance Analysis of Parabolic Trough Solar Concentrator with Helical Tube Receiver - Hamidi, Saad Tami; Mohammed, Jamal Abdul-Kareem; Reda, Laith Mohsen (Al-Nahrain Journal for Engineering Sciences, 2018)
In this paper, the experimental thermal performance for a parabolic trough solar concentrator (PTSC) combined with helical tube receiver and directed by two axes solar tracking system at different amount of water flow rates has been analyzed. The experimental test results of thermal performance with regard to temperature rise of water, useful heat gain and collector thermal efficiency for the PTSC prototype at controlled water flow rates (2.3, 22.5 and 29.4 L/h) are collected. The results show that the increase of water mass flow rates causes decrease in the average water output temperature as (120.8, 63.82 and 46.08oC), respectively, the maximum outlet temperature becomes (160.5, 76, 47) oC, respectively, and thus, the average useful heat gain will be (1249.4, 732, 732.5W), respectively and the average thermal efficiency decreases as (73.021, 49.51 and 44.31 %), respectively. The experimental results show that decrease the water mass flow rate by 74.4%, causes an increase in the thermal efficiency of the PTSC by 64.7%.